Incidence, prevalence, and risk factors for epilepsy, and mortality - Hesdorffer, Dale (Henry Stewart Talks, 2013)
Prevalence and incidence of epilepsy, Etiology of epilepsy, Temporal changes in epilepsy incidence, Risk factors for epilepsy in infants, children and adults, Epilepsy risk in mental retardation, cerebral palsy, autism, Different types of seizures, Traumatic brain injury and seizures, Epilepsy risk after Stroke, CNS infection, Dementia, Brain tumors and migraines, Neuropsychiatric risk factors for epilepsy (ADHD, Depression and anti-depressants, Suicide attempt), Mortality in epilepsy and SUDEP (relation to accidents & injures, adherence to AEDs, predictors of death)